PENGARUH BEBAN KERJA DAN DUKUNGAN REKAN KERJA TERHADAP PRESENTEEISM PADA KARYAWAN GENERASI Z SEKTOR JASA DI BANDAR LAMPUNG - Embun Daudini; Ribhan Ribhan (Yayasan Nusantara Hasana Berdikari, 2026)
Changes in the current workforce composition encourage organizations to pay greater attention to employee well-being, particularly Generation Z, who are beginning to enter and dominate the labor market. This study aims to examine the effect of workload and coworker support on presenteeism among Generation Z employees in the service sector in Bandar Lampung. This study uses a quantitative approach. Data were obtained by distributing questionnaires to 111 respondents who were Generation Z employees working in the service sector in Bandar Lampung. The sampling technique used in this study was purposive sampling. The independent variables in this study are workload and coworker support, while the dependent variable is presenteeism. The data were analyzed using multiple linear regression with the assistance of SPSS. The results show that workload has a negative and significant effect on presenteeism, while coworker support has a positive and significant effect on presenteeism. These findings indicate that variations in presenteeism can be explained by workload and coworker support, while the remaining variation can be explained by other factors outside this study. This study shows that workload and coworker support are factors that play a role in explaining presenteeism among Generation Z employees in the service sector in Bandar Lampung.